Simulation of the heat transfer from the steel samples treated by ion implantation - Гончаров, В.В.; Чукавін, Б.В.; Ненько, М.В. (Eastern-European Journal of Enterprise Technologies, 2010)
In the article the problem of determination of influence of different factors on heat emission of samples, treated ionic implantation is considered. Through the method of renewal of one-dimensional dependences (MROD) force of influence of every output index on the coefficient of convective heat emission is experimentally tested.